Pengaruh Dosis Inokulum Marasmius sp. dan Lama Inkubasi terhadap Kandungan Komponen Serat dan Protein Murni pada Sabut Kelapa Sawit untuk Bahan Pakan Ternak - Endri Musnandar (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2006)
The  objective  of  the  experiment  was  to  find  out  the  best  inoculum  dosage  and incubation  time  for  fiber  component  percentage  and  true  protein  percentage.  The experiment was arranged by a Completely Randomized Design with factorial pattern 4x4, which  the  first  factor  was  inoculum  dosage  (D2,5=2,5%;  D5=5%;  D7,5=7,5%;  and D10=10%) and the second factor was incubation time (W1=1 week, W2= 2 week, W3 = 3 week,  and  W4=  4  week),  the  treatment  combination  were  replicated  3  times  which component  fiber  percentage  and  true  protein  percentage  as  parameters.    All  data  were analyzed by analysis of variance followed DMRT.  The results of experiment showed that there was significant interaction between inoculum dosage and incubation time on fiber component and true protein percentage.  The lowest of fiber component especialy lignin and highest true protein percentage were found  at D3W3 combination treatment, which the fiber componen percentage was NDF (67.63%), ADF (60.50%), selulosa (45.27%), lignin (9.93%), and True protein (8.957%).